Tess - Roman Polanski; Pickles, Carolyn; John Collin; Leigh Lawson; Peter Firth; Richard Pearson; Rosemary Martin; Nastassja Kinski (France, UK Sony Pictures, 1979)
A rural clergyman in 19th century England tells Durbeyfield, a simple farmer, that he is descended from the illustrious d'Urberville family -- now extinct. Or maybe not. Durbeyfield sends his daughter Tess to check on a family named d'Uberville living in a manor house less than a day's carriage ride away. Alec d'Urberville is delighted to meet his beautiful ""cousin"" and seduces her with strawberries and roses. Actually Alec has gotten his illustrious name and coat of arms by purchasing them. Tess too takes up the game of illusion when she finds, loses and finds again her true love Angel.
A young strong-willed peasant girl, becomes the affection of two men, in the end tragically falling into the arms of one.
Gérard Brach
Languages: English, Turkish
Subtitles: Turkish
Keywords: Romance; Drama